Bacillus velezensis WB invokes soil suppression of Fusarium oxysporum f. sp. niveum by inducing particular taxa - Shiqi Luo; Zhigang Wang; Weihui Xu (Annals of Agricultural Sciences, 2023)
Fusarium wilt of watermelon caused by Fusarium oxysporum f. sp. niveum (Fon) results in a substantial economic losses in agriculture. Biological control agents (BCAs) help in controlling the infection of Fon. However, it remains unclear whether the application of BCAs can invoke soil suppression by inducing specific microbial groups concerned with disease suppression to synergistically resist fungal pathogens. The objective of this project was to determine the microbial mechanisms involved in disease suppression by BCAs. Here, we conducted pot experiments to explore Fusarium wilt in watermelon and soil microbial communities in response to different treatments. We found that the application of Bacillus velezensis WB enhanced disease suppression in nonsterilized soil. We further found that disease suppression in the WF treatment was connected to influence on the resident soil microbial communities, explicitly by causing an increase in Hyphomicrobiaceae and Chitinophagaceae. Pathogen suppression by the above two families was further studied in laboratory and pot experiments. The results showed that a synthetic community consisting of specific bacterial taxa effectively decreased the incidence of Fusarium wilt. B. velezensis WB introduction impacts the resident soil microbiome and invokes soil suppression by inducing resident microbes. Our results should help in designing synthetic microbial communities to improve soil function.